(untitled) - Joyner, Rick; (1949-...) (U.S.A, 1994)
When I first shared each of these visions, I was inundated with requests to copy and translate them, and they quickly went around the world. Now, almost two decades later they are being rediscovered, and this book is the result of the growing demand for them again, Much that was prophesied in these visions has come to pass, and the rest seems to be upon us. They now seem more relevant than ever.
Keywords: Private revelations